2014
DOI: 10.1186/1756-9966-33-51
|View full text |Cite
|
Sign up to set email alerts
|

Butein suppresses breast cancer growth by reducing a production of intracellular reactive oxygen species

Abstract: BackgroundButein has various functions in human diseases including cancer. While anti-cancer effects of butein have been revealed, it is urgent to understand a unique role of butein against cancer. In this study, we demonstrate that butein inhibition of reactive oxygen species (ROS) production results in suppression of breast cancer growth.MethodsDifferent breast cancer cell lines were treated with butein and then subjected to cell viability and apoptosis assays. Butein-sensitive or -resistant breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…Cells were treated with different concentrations of naringenin for 24 h and seeded at a density of 5x10 5 /ml in the upper chamber of the 48-well Boyden chamber (Merck Millipore). The lower chamber contained 20% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were treated with different concentrations of naringenin for 24 h and seeded at a density of 5x10 5 /ml in the upper chamber of the 48-well Boyden chamber (Merck Millipore). The lower chamber contained 20% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…For example, butein inhibits the migration and invasion of bladder cancer cells by reducing the expression of extracellular signal-regulated kinase 1/2 and its activities (3). In addition, butein has been found to elevate reactive oxygen species (ROS) levels and trigger apoptosis in neuroblastoma (4) and breast cancer cells (5,6). Moreover, shikonin induces apoptosis in osteosarcoma cells via the generation of ROS (7).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been reported to possess numerous biological activities such as vasorelaxant [6], antitumor [7][8][9][10][11], antiinflammation [10,11], antimalarial [12][13][14], antiplasmodial [13,14] and antioxidant [15][16][17][18][19][20][21]. For instance, butein has shown antioxidant activity against lipid and low-density lipoprotein peroxidation by its free radical scavenging action and metal ion chelation ability [15,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenolic compounds have received considerable attention for their use as a cancer chemopreventive and a chemotherapeutic agent. Previous in vitro studies showed butein cytotoxic and anti-proliferative effects on breast cancer cells, including MDA-MB-231 and MCF-7 [13,53], suggesting that butein might have similar effects in other breast cancer cell lines. However, there is no data comparing the effect of this compound in racially different TNBC cells.…”
Section: Discussionmentioning
confidence: 99%